2017
DOI: 10.1038/ncomms16073
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-tumour immunity requires the interplay between resident and circulating memory CD8+ T cells

Abstract: The goal of successful anti-tumoural immunity is the development of long-term protective immunity to prevent relapse. Infiltration of tumours with CD8+ T cells with a resident memory (Trm) phenotype correlates with improved survival. However, the interplay of circulating CD8+ T cells and Trm cells remains poorly explored in tumour immunity. Using different vaccination strategies that fine-tune the generation of Trm cells or circulating memory T cells, here we show that, while both subsets are sufficient for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(248 citation statements)
references
References 40 publications
(86 reference statements)
13
233
1
1
Order By: Relevance
“…Tumor cells were dynamically surveyed by CD69 + CD103 + CD8 + T RM cells, and T RM cell responses were observed more often and at higher densities in peritumoral skin than in the skin of tumor‐bearing mice. In line with the findings of Enamorado et al (), melanoma development was also suppressed in the majority of mice, irrespective of depletion of T CIRC cells, but protection was most pronounced in mice harboring both T CIRC and T RM cells. These studies clearly affirm the potential of intradermal vaccine‐induced T RM cells to achieve potent protection against skin cancer.…”
Section: Skin‐resident T‐cell Responses In Melanomasupporting
confidence: 90%
“…Tumor cells were dynamically surveyed by CD69 + CD103 + CD8 + T RM cells, and T RM cell responses were observed more often and at higher densities in peritumoral skin than in the skin of tumor‐bearing mice. In line with the findings of Enamorado et al (), melanoma development was also suppressed in the majority of mice, irrespective of depletion of T CIRC cells, but protection was most pronounced in mice harboring both T CIRC and T RM cells. These studies clearly affirm the potential of intradermal vaccine‐induced T RM cells to achieve potent protection against skin cancer.…”
Section: Skin‐resident T‐cell Responses In Melanomasupporting
confidence: 90%
“…Importantly, the density of T RM cells within the tumor environment has been shown to predict for improved survival in a number of cancer types, including advanced‐stage melanoma . In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models . Furthermore, we have recently demonstrated that T RM cells can promote cancer‐immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time .…”
Section: Introductionsupporting
confidence: 59%
“…15 In line with this, recent reports have shown that T RM cells afford potent antitumor immunity in mouse models. 10,13,[16][17][18] Furthermore, we have recently demonstrated that T RM cells can promote cancer-immune equilibrium in mouse skin by keeping dispersed melanoma cells dormant over extended periods of time. 19 Whether T RM cells have a similar function in maintaining tumor dormancy in humans, however, remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in a parabiosis mouse model, one of our groups showed that T RM cells induced by intranasal vaccination are required to control orthotopic head and neck tumor growth [39]. These results obtained with parabiosis experiments have been reproduced by the group of Sancho [10]. Together, these observations suggest that the absence of local T RM induction correlates with lower vaccine efficiency; they highlight the crucial role of these cells in tumor control.…”
Section: Role Of Trm In Immune Surveillance and Immunotherapymentioning
confidence: 81%